Evaluating the Effectiveness of Zero Trust Architecture in Protecting Against Advanced Persistent Threats - Pushpendra Kumar Verma; Bharat Singh; Preety; Shubham Kumar Sharma; Rakesh Prasad Joshi (Advances in Distributed Computing and Artificial Intelligence Journal)
As a paradigm shift in network security, the idea of Zero Trust Architecture has attracted a lot of attention recently. This study intends to investigate the assessment and application of Zero Trust Architecture in business networks. Network segmentation, continuous authentication, least privilege access, and micro-segmentation are some of the basic ideas and elements of Zero Trust Architecture that are covered in this research. By taking a comprehensive approach to network security, the study evaluates how well Zero Trust Architecture mitigates security risks and shrinks the attack surface. It looks into the difficulties and factors to be taken into account when adopting Zero Trust Architecture, including scalability, user experience, and operational complexity. To shed light on the real-world application of Zero Trust Architecture, the paper also investigates empirical data and case studies from real-world scenarios. The influence of Zero Trust Architecture on operational processes and network performance are also be covered, along with recommended practices and various deployment strategies. Additionally, the research assesses how well Zero Trust Architecture conforms to regulatory standards, compliance needs, and existing security frameworks. The results of this study help us comprehend Zero Trust Architecture and its possible advantages and disadvantages. By offering a thorough evaluation framework and useful suggestions for effective implementation, it is helpful to organizations looking to adopt Zero Trust Architecture. The study's findings add to the corpus of information on Zero Trust Architecture and its role in strengthening network security in the face of evolving cyber threats.